Identification and properties of the genes encoding the poly(A) polymerase and a small (22 kDa) and the largest subunit (147 kDa) of the DNA-dependent RNA polymerase of molluscum contagiosum virus - Sonntag, Kai-Christian; Clauer, Ulf; Bugert, Joachim J.; Schnitzler, Paul; Darai, Gholamreza (Virology, 1995)
The DNA-dependent RNA polymerase (DdRP) is an essential enzyme for transcription of molluscum contagiosum virus (MCV), a member of the family Poxviridae which replicates in the cytoplasm of the infected cell. Using PCR technology and oligonucleotide primers, corresponding to two conserved domains (RQP[T/S]LH and NADFDGDE) of known largest subunits of eucaryotic and procaryotic DNA-dependent RNA polymerases, the DdRP gene of the genome of molluscum contagiosum virus type 1 (MCV-1) was identified and characterized. The oligonucleotide primers were designed according to the coding usage statistics of known open reading frames of the viral genome. The gene for the largest subunit of DdRP was localized within the DNA sequences of a part of the Bam HI DNA fragment A (BamHI/HindIII DNA fragment A8a; 13.5 kbp, 0.454 to 0.625 viral map units) of the MCV-1 genome. The DNA nucleotide sequence analysis of a part (6709 bp) of this DNA fragment revealed the presence of 12 open reading frames (ORFs). It was found that ORF-4 (nucleotide position (NP) 2586 to 6452) and ORF-1 (NP 1192 to 1752) encode two polypeptides comprising 1289 (147 kDa) and 187 (22 kDa) amino acid residues, respectively. The comparative analysis of the amino acid sequences of these ORFs to the amino acid sequences of two subunits (RPO1, 147 kDa and RPO6, 22 kDa) of the DdRP of vaccinia virus revealed high amino acid sequence identity/similarity of about 71.9/21.5% and 46.5/39.6%, respectively. In addition it was found that the putative gene position of ORF-11, which is located on the lower strand between the loci of the ORF-1 and ORF-4 (NP 4256 to 4657, 134 aa, 15 kDa), is similar to the genomic arrangement of the JSL protein of vaccinia virus and L5L of variola virus. The value of amino acid sequence identity/similarity between the product of ORF-11 and the corresponding gene of vaccinia virus (J5L) was found to be 43.2/28.8%. The analysis of the amino acid sequence deduced from ORF-3 (NP 261 to 1289, 343 aa, 40 kDa), which is located upstream from the locus of the RPO6 of the MCV-1 genome, showed significant identity/similarity (47.5/35.7%) to the amino acid sequence of the 40-kDa subunit of the poly(A) polymerase (PAP2) of vaccinia virus. The arrangement of the identified loci of the PAP2, RPO6, ORF-11, and RPO1 of the genome of MCV-1 shows that this particular genomic region of the molluscum contagiosum virus and vaccinia virus is colinear.
Elektronische Reproduktion der Druck-Ausgabe 25. Mai 2002
Gesehen am 05.09.2024